Digitalisasi Komunikasi Bisnis UMKM sebagai Upaya Meningkatkan Daya Saing - Fitri Argarini (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
Communication plays a crucial role in organizations as it influences interactions between individuals and the achievement of organizational goals. In the context of organizations, communication occurs in three main forms: verbal, non-verbal, and written. Each of these forms plays a role in shaping perceptions, understanding, and supporting appropriate decision-making. However, misunderstandings often arise due to differences in perception between individuals or groups, which can affect work effectiveness and relationships within the organization. This study aims to explore the role of verbal, non-verbal, and written communication in fostering effective relationships within organizations. Using a qualitative method and literature review, this research delves deeply into the communication phenomena within organizations. The findings indicate that clear and effective communication whether verbal, non-verbal, or written can enhance employee performance, facilitate the flow of information, and strengthen cooperation within the organization. Therefore, it is essential for organizations to understand and implement communication effectively to reduce the potential for misunderstandings and improve work effectiveness and the achievement of organizational goals.